Fractal Theory (3CSS JTcjd GdYeQGf GdMVGQi GdMjhi GdeSJOGe h JWhQg PGJjkG HGSJNOGe gfOSI GdcShQjGJ (B/ s - (3SGdi YGOd GMeO Ydis; (3SYGO jhSa MSfjf HTfOi (B: s; (3WGQb CHh GdSYhO Rci (B: s; (3gTGe eMeO eMeO GdHQedLi (B: s ((3GdbGgQI (B: s (3SGdi YGOd GMeO Ydi (B: s, 2018)
(3jbOe GdHMK eONd eNJda ddJYGed eY GdYeQGf Ydi Gfg cGFf Mi MVGQi h djS ccjGf eGOi HMJ HgOa GdhUhd ddJhGDe GdCeKd eY GdWHjYI GdHTQjI(B: (3ai VhA Gfg GUHM eaJbOG ddQhM h GdMjGI h ZjQ eQGYi ddeJZjQGJ GdeNJdaI ai GdCfXeI GdELJeGYjI(B. (3h ai gPG GdSjGb jfGbT GdHMK GdHjFI GdYeQGfjI cefXheI ZGjI ai GdJYbjO h GdJi JVe GdYOjO ef Gdbhi h GdGfXeI GdJi JDKQ ai GdMjR GdYeQGfi HWQjbI eHGTQI Gh ZjQ eHGTQI h cjajI GdJYGed eY Jdc GdGfXeI GdYeQGfjI h GdELJeGYjI GdeYbOI(B. (3JHYkG dPdc(B: (3jgOa GdHMK HTcd QFjSi Edi GjLGO h GSJMOGK CSS GdJTcjd GdYeQGfi GdMj h GdMVGQi ef MjK GdfTGI h GdJWhQ ai GdJTcjd(B: (3h Pdc dEjLGO NUGFU h GfXeI GdHfjI GdGhdjI ai GdYeQGf h gi CfXeI eGOjI eSJhMGI ef CfXeI GdWHjYI h CfXeI GdcjGf GdeYfhi GdMjhjI h GddGeGOjI(B. (3jJHY Pdc GdhUhd Gdi Gdgjcd GdMjhi (B- (3GdeYjTi ef NdGd JMdjd Gdfeh GdPGJi dJdc GdHfjI GdhdjI ai GdYeQGf HGSJNOGe fXQjI GdcShQiGJ ceONd fXQi aYGd ai dOQGSI Gdfeh GdPGJi ddYeQGf h JhbY GdGeJOGO GdeSJbHdi dgs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJNWjW GdEbdjei h GdYeQGfi (B- (3bSe GdJUeje GdYeQGfis
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdGfXeI GdYeQGfjIs; (3GdYeQGf GdMVGQi GdMjhi GdeSJOGe s; (3gfOSI GdcShQjGJs